Psychosocial Challenges as Predictors of Life Satisfaction and Coping Strategies Among Female Sex Workers: A Mixed Design Study - Tesfaw, Fasil Asmamaw; Patel, Dipal (Journal of Neonatal Surgery, 2025)
The purpose of the study was to examine the influence of psychosocial challenges on the life satisfaction and coping strategies among female commercial sex workers in Hawassa City Administration. Mixed approach with concurrent design was applied integrating quantitative data with the qualitative data simultaneously. Two hundred sixty five randomly selected and sixteen purposely selected participants involved in the study. Data was collected through questionnaires and Focus Group Discussion (FGD). Quantitative data was analysed through multiple regression, but the qualitative data was analysed through thematic content analysis. The findings demonstrated that there was main effect of stigma-discrimination on the life satisfaction of FSW with 22% (R-Square= .22, F (1,264) = 74.43, Beta = -.47, p = .000.In addition to interaction effects were found between stigma-discrimination and risk sexual behaviours, 31% (R-Square= .31, F (2,262) = 56.68, Beta = -.70; p = .000 as well as the interaction effect between stigma-discrimination, risky sexual behaviours and stress with 32% (R-Square= .32, F (3,261) = 40.42, Beta = -.71; p = .000. Concerning the impacts of psychosocial challenges on coping strategies, risky sexual behaviour had main effect 18 %( R -Square= .18, F = (1,264) =57.88 Beta =-.43, P = .000; the combination of risky sexual behaviours and stigma-discrimination was 22% (R-Square= .22, F (2,262) = 35.94, Beta = -.57; p = .000; and the interaction effect of risky sexual behaviours, stigma-discrimination and stress had 24% (R-Square= .24, F (3,261) = 26.86, Beta = -.66; p = .000. Additionally, the findings derived from the qualitative approaches supported the findings obtained from the quantitative data. Implications are discussed to mitigate psychosocial challenges among FSW to ensure their life satisfaction and coping strategies.